Spectrophotometric Determination of Sulfathiazole Using 2,4 â€“dinitrophenylhydrazine as Coupling Reagent - Israa T. Humedy; Ismael M. Ali (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
A rapid, sensitive and selective spectrophotometric method was developed for determination of sulfathiazole (STHZ) in aqueous solution. The method is based on the  oxidative coupling reaction with 2,4-dinitrophenylhydrazine (2,4-DNPH) in a basic medium (pH 10.9) in the presence of  potassium periodate to produce an intense orange colour, soluble in water , stable product and absorbs at 492 nm. Beer's law was in the linear range 2.0-28.0 Î¼g/ml of sulfathiazole, the molar absorptivity, SandellÊ¼s sensitivity index and detection limit were 1.1437 Ã—104 liter. mol-1.cm-1,0.0223 Î¼g.cm-2 and 0.1274 Î¼g/ml respectively. The RSD value was  0.75 - 1.12 % depending on the concentration. This method was applied successfully to the determination of sulfathiazole veterinary injection liquid solution (bio prime) with average recovery of not less than  100.38  %.